Steady Comparisons with References of starik, starichok ‘Old Man,’ starukha, starushka ‘Old Woman’ in Russian Language Picture of the World (on Background of Chinese Language) - L. Zhang (Научный диалог, 2017)
The analysis of steady comparisons with the references of starik , starichok ‘the old man,’ starukha , starushka ‘the old woman’ is made on the background of the Chinese language. Based on the analysis, the extension of the set of grounds for each reference was revealed in comparison with units recorded in the dictionary, and also similarities and differences in the grounds for comparisons in the two linguistic cultures were identified. It is suggested that similarities are due to universal objective characteristics of the elderly: their physical condition, certain features of appearance and behaviour. The differences of the used grounds for the same reference in two languages lie in the fact that, firstly, the views about the mind, the wisdom of the old man in the minds of the representatives of the two cultures are diametrically divergent. The old man in the view of Russian native speakers - the standard of wisdom, and for native Chinese speakers - no. Secondly, lacunar grounds for comparisons for the Russian linguistic culture are ‘slow’ and ‘stubborn’ about the old man. Thirdly, the grounds ‘funny’ and ‘cute’ in relation to the old man are also not used in the Russian steady comparisons. These differences are due to the influence of Chinese media on the one hand, promoting active lifestyle of older people (‘funny’ and ‘cute’), on the other hand, introducing into linguistic consciousness of native speakers the image of the evil older woman (‘grumpy’ and ‘evil’).